KONSEP PENDIDIKAN MENURUT AL-GHAZALI DAN RELEVANSINYA DALAM PENDIDIKAN DI INDONESIA - Arista, Rizki Noura (IAIIG Cilacap, 2019)
Islamic education is a means for the formation of people who are able to know their Lord and serve Him. In al-Ghazali's view it was stated that humans who were educated in the education process to be smart, but immoral, that person was categorized as a fool, whose life would be difficult.In general, this study aims to determine the concept of Islamic religious education according to Imam Al-Ghazali, The specific purpose of this study is to find out al-Ghazali's thoughts about science, and to know al-Ghazali's thoughts about the concept of Islamic education. To answer the purpose of this research in this literature research method used qualitative data analysis techniques namely reflective thinking data analysis, namely data analysis techniques with the process of thinking back and forth. In addition, to analyze existing data, the author also uses a comparative method, which examines the factors with the situation or phenomenon under investigation and compares one factor to another.The findings of this study show that science is a source of happiness in the world and the hereafter. With science will make humans become noble and honorable beings compared to other creatures. While al-Ghazali's thoughts on the concept of Islamic education are: 1) educational goals according to al-Ghazali must lead to the realization of religious and moral goals, 2) educators not only teach the sciences, but more importantly also shape the character and personality of their students with morals and Islamic teachings, 3) students intend to seek knowledge solely to worship Allah SWT, 4) methods and media used in the learning process, according to al-Ghazali must be seen psychologically, sociologically, and pragmatically in the framework success of the learning process.